Data and modelling for the Territorial Impact Assessment (TIA) of policies - Medeiros, E. (Handbook of computational social science for policy, 2023)
Territorial Impact Assessment (TIA) is still a ‘new kid on the block’ on the panorama of policy evaluation methodologies. In synthesis, TIA methodologies are thematically holistic, multi-dimensional and require the analysis of a wide pool of data, not only of economic character, but also related with social, environmental, governance and planning processes, in all territorial scales. For that, TIA requires a wealth of comparable and updated territorialised data. Here, data availability is often scarce in many of the selected analytic dimensions and respective components, to assess territorial impacts in a given territory, in particular in the domains of governance, planning and environment. In this context, this chapter presents a list of non-traditional potential indicators which can be used in existing TIA methodologies, Moreover, the analysis was able to show how important can be the use of non-traditional data, to complement mainstream statistical indicators associated with socioeconomic development trends. However, for the interested scientist, the dispersal of existing non-traditional data per a multitude of sources can pose a huge challenge. Hence the need of an online platform which centralises and updates non-traditional data for the use of all interested in implementing TIA methodologies.